Assessment of spirometric and cardio-respiratory values of Kenyan distance runners - Mwangi, F. M. (The Russian Journal of Physical Education and Sport, 2017)
Some studies have reported significant relationships between some spirometric, cardio-respiratory and endurance performance variables. This study therefore sought to determine the status of these values among Kenyan distance runners who have dominated endurance running events internationally. Methods: Fifteen (10 male, 5 female) purposively selected elite Kenyan runners were instrumented in baseline spirometry and an incremental treadmill test to exhaustion with respiratory gasses and heart rate assessments. Results: One sample t test showed that most spirometric values are not significantly different from predicted (p > .05). Relative maximum oxygen consumption (VO2max) for males (64.4 ± 4.9) and females (50.0 ± 1.9) ml/kg/min rated superior and excellent on cardio-respiratory fitness classification norms, while maximum heart rate was significantly lower than predicted. Pearson correlation analyses showed that some spirometric variables have significant relationship with oxygen consumption at submaximal level; VE; r= .792, p=001, FEV1; r=.658, p=.010, FVC; r=.741, p=.002 and PEF; r=.625, p=.017. Conclusions: Kenyan distance runners` spirometric values can be predicted by commonly used equations for general population. However, the runners have superior to excellent rating of aerobic capacity as well as high sustainable percentage of the same. These may point to enhanced gaseous exchange capacity/properties such as more pulmonary capillarisation, less shunts, and / or favourable hemodynamics. Recommendations: More studies are needed to explore how spirometric and cardio-respiratory variables contribute to overall endurance running performance.